Implementasi Metode Qiroati Terhadap Kemampuan Membaca Al-Qur’an di MTs Tahfizh Al-Falakiyah Kota Bogor - Ratu Siti Naila Muna; Indry Nirma Yunizul Pesha; M. Kholil Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
To be a superior and qualified Muslim, of course you must be able to read the Al-Qur'an clearly and fluently. The use of methods is an important factor in improving the ability to read the Al-Qur'an. The Qiroati method is a fairly old method, where the Qiroati method emerged and was pioneered by K.H. Dahlan Salim Zarkasyi. MTs Tahfizh Al-Falakiyah is one of the school that uses the Qiroati method in its teaching and learning activities, because the Qiroati method is a fast and precise method for learning to read and write the Al-Qur'an. This research aims 1) to determine the implementation of the Qiroati method on the ability to read the Al-Qur'an, 2) to determine the development of students' abilities in implementing Al-Qur'an Reading Learning using the Qiroati Method 3) to determine the supporting and inhibiting factors for implementing the Qiroati method in reading the Al-Qur'an, 4) to find out solutions to the factors inhibiting the implementation of the Qiroati method in reading the Al-Qur'an. This research method uses qualitative research with a descriptive approach, the main characteristic of this research is that the researcher is directly involved in the field, acts as an observer, creates categories of actors, observes phenomena, records them in a research book. Data collection techniques are interview and documentation techniques, using data reduction analysis, data presentation and conclusions. The research results show that 1) the implementation of the qiroati method on the ability to read the Al-Qur'an has three steps, namely planning, implementation and individual evaluation. 2) The development of students' ability to read the Koran is quite good and significant 3) there are several supporting factors, one of which is professional teaching staff, the facilities provided by the school and there are also several inhibiting factors that come from teachers and students. 4) the solution to the inhibiting factors is regular training and development for the teaching team, more complete learning tools, and creating a conducive and enjoyable learning situation. It can be concluded that the Qiroati method applied at MTs Tahfizh Al-Falakiyah Bogor City is very suitable and appropriate, this is proven by the 2024 EBTAQ test results data from 7A of 28 students 2 students who failed, 7B of 27 students 5 students who failed, 7C of 28 students 5 students who failed, 7D of 31 students 5 students who failed, 7E of 31 students, 5 students who failed. So out of a total of 145 grade 7 students, there are 22 students who have not passed the test. Then from class 8A data of 28 students 1 person failed, 8B of 31 students 3 people failed, 8C of 31 students 3 people failed, 8D of 29 students 3 people failed, 8E of 28 students 2 people failed. So out of a total of 147 grade 8 students, there are 12 students who have not passed the test. Finally, data from class 9A, all 28 students passed, 9B from 26 students all passed, 9C from 28 students all passed, 9D from 31 students all passed, 9E from 31 students all passed. So out of a total of 144 grade 9 students, all managed to graduate. This proves a significant result, because there is an increase in success in the test which increases with each class.